P.006 Keeping neurosarcoidosis on the differential. (17th June 2016) - Spinelli, E; Blevins, G; Mailo, J; Atilano, L; Leonard, H; Yeh, EA; Kolski, H
Abstract : Background: Sarcoidosis is a multiorgan autoimmune disease characterized by the presence of non-caseating granulomas. The diagnosis can be difficult, particularly with central nervous system (CNS) involvement, and pathology outside of the CNS has to be carefully evaluated. Early and correct diagnosis is crucial for appropriate management particularly in children where sarcoidosis and neurosarcoidosis are rare. Methods: We describe a 16 year old previously healthy boy who presented with progressive pyramidal neurological signs and symptoms localizable primarily to the brain stem. Results: Initial imaging revealed striking brainstem, as well as cerebral, cerebellar and spinal cord perivascular enhancement. Lung involvement was subclinical with a miliary pattern on chest imaging and needle biopsy revealed an interstitial lymphocytic infiltration. Extensive serum and CSF rheumatological, autoimmune and infectious investigations were noncontributory. Serum ACE levels were at first within normal limits. Steroid treatment stabilized symptoms and perhaps coincidentally, separate rituximab treatments were followed within days by vertigo (with a new pontine lesion) or a respiratory decompensation. A wedge lung biopsy revealed granulomatosis. Current treatment consists of mycophenolate, methotrexate with a prednisone wean. Conclusions: This case report reinforces the varied manifestations and mimics of sarcoidosis (including CLIPPERS) and highlights the need for a high index of suspicion despite apparently negative investigations.